Tingkat Motivasi Belajar Siswa SMP di Masa Pandemi dalam Pembelajaran Pendidikan Agama Islam - Wiwied Widiyanti; Ummah Karimah; Fina Zahra Efendi; Siti Annisa Nur Fadillah; Putri Lestari Fitriana; Ahmad Zahran; Yazid Ulumi (Gunung Djati Conference Series, 2022)
This study aims to obtain an overview of the level of learning motivation of students at Al-Hikmah Islamic Junior High School Pondok Cabe Ilir, South Tangerang in the academic year 2021-2022 during the pandemic in learning Islamic religious education. The instrument of this research is a student learning motivation questionnaire. This type of research is descriptive quantitative with survey method. The subjects in this study were Al-Hikmah Middle School students, totaling 59 students. The data analysis technique used is categorization according to Azwar which is based on the ordinal category model. This category is divided into 5, namely very high, high, medium, low, and very low. The results of this study indicate that there are 19 students with 32.2% who have a very high learning motivation category, 37 students who get 62.7%, who have high learning motivation, 3 students who get 5.1%, who have high motivation. learning is in PAI learning. From the results of this study, it can be said that the level of student learning motivation in Islamic religious education subjects during the pandemic is quite high.